Otimização de estruturas metálicas formadas por perfis "I" soldados - Drehmer, Gilnei Artur (2005)
The main goal, in the design of structures, it is to minimize the cost while it is satisfied the criteria of codes and specifications. traditionally, the design has been resolved for trial and error, dictated by the code limitations and guided by the experience and intuition of the engineer. However, researchers have been developing analysis and optimizing tools to aid the engineers in some of the difficult processes of calculation and to help to obtain "the best" design. In the last decades, the innovation in those calculation tools has been growing with the increase of computers speed. As cost of the steel structures is directly linked to the weight, is presented in this work the development and the implementation of a formulation for structural optimization of welded I sections, using as base data commercials thickness in the Brazilian market, and doing the calculations according with the Brazilian Code NBR 8800/1986. The proposal is worked on dimensions of sections, loads and materials properties used in the steel market. To minimize the weight of the welded I section is used and heuristic method, Simulated Annealing, some examples are presented to verify the formulation implemented, as well as comments, conclusions and suggestions for continuity of this research